Encuesta de los pseudococcidos de Cuba. Resultados del periodo 2001-2002 - Blanco Rodriguez, E.=700 1 Perez Vicente, I.; Rodriguez Castro, A.M.
(Es, En)
Ilus., 8 ref.
Keywords: ENCUESTA; PSEUDOCOCCIDAE; HUESPEDES; CUBA; DYSMICOCCUS BISPINOSUS; DYSMICOCCUS HURDI; INDICE DE INTERCEPCION; SIMILITUD